Contribuição ao estudo dos níveis de energia em sistemas contendo íons Ln3+ - Oliveira, Yuri Álisson Rodrigues de (2016)
A new approach to describe the crystal field interaction in compounds that contains trivalent lanthanide ions is presented. It is considered the electrostatic balance of the optically active site, the effective charge of the central ion and the sign of crystal field parameters (CCP) as determinant factors in the crystal field interaction. The method of the first equivalent neighbours (MENN) was reformulated, and improvements in predicting the CCP and energy levels 7FJ of Eu3+ could be realized. Moreover, it was possible to predict the lanthanide-nearest neighbour interaction of load factors (Ln-NN), the maximum coverage of the wave functions of the interacting ions and energy levels levels structure of the 7FJ of Eu3+. The physically acceptable limits are designed to load factors and the maximum overlap of the wave functions of the interacting ions. The compounds studied have high symmetry and exhibit a first neighbourhood consisting of oxygen ions, fluorine or chlorine. The use of secular determinants solutions of the energy matrices served as an excellent theoretical framework for the development of the method, which is applied based on the simple overlap model (SOM). This allowed the description of the interaction of the crystalline field by a nonparametric method and simple application. In addition, it was predicted the wave functions overlap factor of the interacting ions, the total effective bonding charge of Eu3+, and the relationships and trends of the crystal field interaction with the chemical species of the NN and the type of Ln that makes up the main host matrix. Finally, it was possible to remodulate the MENN at a more theoretical method by using theoretical data. The results served to confirm the efficiency and accuracy of MENN in describing the interaction of the crystal field on systems containing trivalent lanthanide ions.